Paul: Law and Salvation - Larsson, Edvin (New Testament studies, 1985)
From F. Chr. Baur and onwards, New Testament scholarship has laid strong emphasis on the difference between the Paul of the letters and the Paul of Acts. A few examples will suffice to illustrate this approach. The real Paul, the Paul of the letters, claims to be an apostle. In Acts he is depicted as subordinate to the Twelve, for whom the title apostle is reserved. In Galatians and Romans Paul takes up a strongly polemical attitude to the Jewish torah and to circumcision. The Paul of Acts circumcizes Timothy (16. 3). And he declares his solidarity with the law, the prophets and the people of Israel (23. 6; 24. 14 f.; 26. 6, 23; 28. 21). In his epistles Paul strongly emphasizes the significance of the death of Christ. He proclaims its atoning effect for all mankind (Rom 3. 24 ff.; 5. 6 ff. 1 Cor 1. 18 ff.; 15. 3; 2 Cor 5. 18 ff.; Gal 3. 13). The author of Acts seems to regard the suffering and death of Jesus, the servant of God, almost as a test, which he had to undergo before ‘entering upon his glory’. To be sure, the death of Christ is also by Luke described as the act through which he won the church for himself (20. 28). And the missionary message in Acts contains the statement that he died according to the Scriptures (3. 18; 13. 27–29). It is, nevertheless, obvious that the death of Christ does not receive the same comprehensive interpretation in Acts as in the Pauline epistles.